(untitled) (Experimental biology, 2015)
It was found that a new group of polyphenols – salvestrols are strong anticancer agents. A particular enzyme – cytochrome P450 CYP1B1 presenting in all types of human cancer cells converts salvestrols to the strong anticancer toxin piceatannol, which kills cancer cell (apoptosis). This toxin is not synthesized in normal healthy cells. Salvestrols are synthesized in fruits and green leaves of a range lants.